Cobalt-ferrite nanobowl arrays : curved magnetic nanostructures - Srivastava, A. K. (2014)
Novel magnetic cobalt ferrite nanostructures with curved surfaces (i.e., nanobowls and hollow nanospheres) in a periodic array have been fabricated by in situ reduction of a cobalt and iron salt solution mixture in the interstitial spaces of three-dimensional, close-packed, polystyrene sphere templates. The effect of the shape created by this nanostructure and magnetocrystalline anisotropy introduced by suitable annealing were used to tailor the coercivity to values relevant to high-density data-storage applications.